Implementasi Kebijakan Dana Bantuan Operasional Sekolah di Dinas Pendidikan dan Kebudayaan Daerah Kabupaten Morowali Utara - Rais Sikki; Mustainah Mustainah; Nawawi Natsir (Journal of Innovative and Creativity, 2025)
The study purpose was to analyze the implementation of the School Operational Assistance (BOS) fund policy at the Department of Education and Culture of North Morowali Regency. This policy aims to support school operational activities and improve the quality of education by ensuring financial assistance is used effectively and transparently. Materials and methods. The study employed a qualitative descriptive method to provide an in-depth understanding of the BOS fund implementation process. Data were collected through observation, in-depth interviews, and documentation from five key informants consisting of education officers and BOS management staff. The analysis followed Miles, Huberman, and Saldaña’s interactive model, which includes data condensation, data display, and conclusion drawing. Edward III’s policy implementation theory covering communication, resources, disposition, and bureaucratic structure served as the analytical framework. Results. The findings indicate that the implementation of the BOS policy in North Morowali Regency remains less effective. Weak supervision, limited human resources, insufficient monitoring and evaluation budgets, and the absence of strict sanctions for fund misuse were identified as the main constraints. Although communication between the education department and schools has improved through meetings and digital media, the overall implementation still lacks optimal control and consistency in financial accountability. Conclusions. To enhance the effectiveness and accountability of BOS fund management, it is recommended that the Department of Education increase the number and competence of supervisors, allocate a larger budget for regular monitoring and evaluation, and enforce stricter sanctions against misuse. Strengthening human resource capacity, institutional transparency, and compliance mechanisms will ensure that the BOS program achieves its goal of improving the quality and equity of education in North Morowali Regency